Erfaringer fra lærings- og mestringskurs for foreldre til premature barn - Cheetham, Nina Bøhle; Hanssen, Tove Aminda (Nordisk tidsskrift for helseforskning, 2016)
Experiences with parent education for parents of premature children The Neonatal Intensive Care Unit and the Learning and mastery center (LMS)/UNN has since 2004 offered parent education on topics as interaction, play, communication and feeding challenges as well as exchange of experience. The aim of this study is to systemize and analyze feedback from parents who have attended the courses. The study has a descriptive design. The selection are course attenders at LMS courses from 2006–2012. An evaluation survey was distributed through Quest back. Data were analyzed through SPSS. Open answers were analyzed through content analysis. A total of 56 persons participated. The majority (86%) reported satisfaction with the themes and 46% reported change in lifestyle. Meeting other parents was reported as useful. Some wished for an increased focus on topics like transition to school and daycare and on future challenges. Some suggested parent education as standard follow up. Parent education seems to meet expectations and the adjustments of the courses seem to have been successful. Feedback from parents suggests a need for more follow up.